A STUDY OF SPEECH ACTS IN “CALL ME BY YOUR NAME” MOVIE: Speech Act, Call Me by Your Name Movie. - Novi Sriwulandari; Muhammad Ainul Yaqin (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2021)
The part of pragmatics that is learned by the students is speech act. Speechact is using utterances to perform some actions, in any occasions speech actemerges in uttterances like in the movie, talk show, novel and many others.Thisstudy intend to analyze speech act used by one of the main characters in “Call me by Your Name Movie movie” movie script. In the analysis is to investigate what acts emerge behind the utterances and the impacts for the hearer after the utterances is stated. The statements of research problem are: 1) what are the illocutionary actsused by Elio and oliver as one of the main characters in Frozen movie script? The Elio and Oliver as one of the main characters in “Call me by Your Name Movie movie” script, and the next purpose is to describe illocutionary act used by Elio and Oliver as one of the main characters in “Call me by Your Name Movie movie” movie script.